RixsToolBox: software for the analysis of soft X‐ray RIXS data acquired with 2D detectors. (2nd February 2017) - Kummer, K.; Tamborrino, A.; Amorese, A.; Minola, M.; Braicovich, L.; Brookes, N. B.; Ghiringhelli, G.
Abstract : A software package for the analysis of resonant inelastic X‐ray scattering data acquired with two‐dimensional detectors is presented. Abstract : A software with a graphical user interface has been developed with the aim of facilitating the data analysis for users of a new resonant inelastic X‐ray scattering (RIXS) spectrometer installed at the ESRF beamline ID32. The software is organized in modules covering all relevant steps in the data reduction from a stack of several hundred two‐dimensional CCD images to a single RIXS spectrum. It utilizes both full charge integration and single‐photon centroiding to cope with high‐flux and high‐resolution requirements. Additional modules for further data analysis and the extraction of instrumental parameters are available. The software has been in routine use for about a year now and in that time many additional features have been incorporated. It now meets the users' need for an easy‐to‐use data analysis tool that allows looking at and understanding data as it is acquired and thus steering users' experiments more efficiently.